2011
DOI: 10.1038/npp.2011.230
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropeptide Y (NPY)-ergic System is Associated with Behavioral Resilience to Stress Exposure in an Animal Model of Post-Traumatic Stress Disorder

Abstract: Converging evidence implicates the regulatory neuropeptide Y (NPY) in anxiety-and depression-related behaviors. The present study sought to assess whether there is an association between the magnitude of behavioral responses to stress and patterns of NPY in selected brain areas, and subsequently, whether pharmacological manipulations of NPY levels affect behavior in an animal model of PTSD. Animals were exposed to predator-scent stress for 15 min. Behaviors were assessed with the elevated plus maze and acousti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
201
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(219 citation statements)
references
References 78 publications
(77 reference statements)
16
201
0
2
Order By: Relevance
“…Therefore, in this study, for a stressor (predator scent) a dirty cat litter was used and a clean cat litter was used as a situational reminder. Like Cohen et al [22], also in this study it had been found out that the anxiety index was significantly higher in the stress group. Our data also demonstrated that the cat litter test was a reproducible experiment where the rats were subjected to a dirty cat litter had higher anxiety The expression level of muscarinic M 1 receptor subtypes in rat brain Marmara Medical Journal 2017; 30: [162][163][164][165][166][167][168] indexes when subjected to the clean cat litter, a situational reminder.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, in this study, for a stressor (predator scent) a dirty cat litter was used and a clean cat litter was used as a situational reminder. Like Cohen et al [22], also in this study it had been found out that the anxiety index was significantly higher in the stress group. Our data also demonstrated that the cat litter test was a reproducible experiment where the rats were subjected to a dirty cat litter had higher anxiety The expression level of muscarinic M 1 receptor subtypes in rat brain Marmara Medical Journal 2017; 30: [162][163][164][165][166][167][168] indexes when subjected to the clean cat litter, a situational reminder.…”
Section: Discussionsupporting
confidence: 79%
“…There is an emerging body of research examining biological markers for resilience, including glucocorticoid receptors (Wagner, Marinescu et al 2012) and neuropeptides (Kozlovsky, Matar et al 2009, Cohen, Liu et al 2012). …”
Section: Resilience and Depressionmentioning
confidence: 99%
“…Many studies on animal models and humans have confirmed the beneficial role of NPY in mediating resilience and vulnerability to stress and anxiety. Animals with PTSD-like behaviors showed a significant down-regulation of NPY in several brain regions including the amygdala and hippocampus, and centrally administered NPY reversed the negative behavioral effects of predator-scent stress (Cohen et al, 2012). Human studies found that, under uncontrollable stress induced by harsh military training, plasma NPY levels were markedly increased, and higher NPY levels were associated with better behavioral performance and stress response (Morgan et al, 2000(Morgan et al, , 2002.…”
Section: Npymentioning
confidence: 99%